Predictors of 007 triphosphate concentrations in dried blood spots in persons with hepatitis C and active drug or alcohol use. (23rd February 2022) - Brooks, Kristina M.; Castillo-Mancilla, Jose R; Morrow, Mary; Mawhinney, Samantha; Rowan, Sarah E; Wyles, David; Blum, Joshua; Huntley, Ryan; Salah, Lana; Tehrani, Arya; Jimmerson, Leah C; Roon, Laura; et al.
Abstract: Background: Sofosbuvir is converted to its active form, 007 triphosphate (007-TP), within cells. To date, the association between treatment adherence and 007-TP in dried blood spots (DBS) and factors that influence this relationship remain unknown. Objectives: To examine relationships between adherence and 007-TP concentrations in DBS and identify factors that influence 007-TP in DBS. Methods: Persons with HCV or HIV/HCV coinfection and self-reported drug and/or alcohol use were randomized to one of two technology-based approaches for monitoring 12 week adherence to once-daily ledipasvir/sofosbuvir. Convenience blood samples were collected every 2 weeks during treatment. 007-TP in DBS was quantified using LC/MS and analysed using mixed-effects models. Results: A total of 337 observations were available from 58 participants (78% male; 21% black; 22% Hispanic/Latino; 26% cirrhotic; 78% HIV-coinfected). The mean half-life of 007-TP in DBS was 142 h (95% CI 127–156) and concentrations increased by 7.3% (95% CI 2.2–12.6) for every 10% increase in between-visit adherence. Geometric mean (95% CI) 007-TP concentrations in DBS were 301 (247–368), 544 (462–639) and 647 (571–723) fmol/punch by adherence categories of ≤50%, >50 to ≤80%, and >80%. Adherence, time on therapy, increasing age and decreased estimated glomerular filtration rate were associated with higher 007-TP, whereas increased time since last dose, male sex, black race and higher BMI were associated with lower 007-TP. Conclusions: 007-TP has an extended half-life in DBS and concentrations increased with adherence. Further research is needed to examine additional factors that affect 007-TP and the clinical utility of this measure.